Āzādī de mujāhid likhārī : taḥrīk-i Pākistān te Panjābī adab - Malik, Shahbāz, 1937- (Merī Lāʼibrerī ;, 1981)
Biographical sketches of noted Panjabi poets who were active in the Pakistani Movement; includes selections from their works.